The Postharvest Safety and Quality of Fresh Basil as Affected by the Use of Cypriot Oregano (Origanum dubium) Extracts - Xylia, Panayiota; Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2024)
The use of natural products (including essential oil—EO from medicinal and aromatic plants) on fresh commodities such as leafy greens has gained a lot of attention due to the beneficial effects of those products. However, fresh herbs are highly perishable commodities, and very little is known for their postharvest preservation. The present study aimed to (i) investigate the effects of Cypriot oregano (Origanum dubium) EO and hydrosol (at different concentrations and times of application) on fresh basil’s quality attributes and preservation and (ii) examine the efficacy of selected doses of O. dubium EO and hydrosol against two major foodborne pathogens inoculated on fresh basil stored at 4 °C for six days. The results of the current study indicated that the application of O. dubium EO at high concentrations in combination with a longer dipping time presented a less aromatic (less basil-like aroma) and preferable commodity, whereas hydrosol application resulted in a more acceptable and marketable commodity. In addition, an increase in antioxidant capacity and ascorbic acid content were observed with the EO, whilst hydrosol application was found to decrease basil’s antioxidant capacity. Both investigated products (EO and hydrosol) where found to present great antibacterial activity against Salmonella enterica and Listeria monocytogenes inoculated on fresh basil even six days after the application. Overall, the investigated natural products (i.e., O. dubium EO and hydrosol) could be considered alternative sanitizing agents during the postharvest processing of fresh basil, whilst preserving and/or improving its nutritional value (i.e., an increase in antioxidants or flavonoids). However, caution should be taken when using it at high concentrations; thus, further research is needed for future commercial-scale use and on other fresh produce.
Keywords: basil; dittany; essential oil; postharvest safety and quality; hydrosol; fresh herbs